Experiments of the saturated Ni-like x-ray lasers driven by a double 75 ps laser pulse - Zhang, J; Wolfrum, E; MacPhee, A; Lin, J; Key, M; Lewis, C; Nilsen, J; O'Rourke, R; Smith, R; Tallents, G; Wark, J (1999)
We report here the experiments of the saturated Ni-like x-ray lasers at 14 -6 nm from a refraction compensating double target driven at 20 TW.cm(-2) by a pair of 75 ps Nd-glass laser pulses separated by 2.2 ns. The output source size as well as the time history, divergence, energy and spatial profile of the output beams of the Ni-like x-ray lasers have been fully characterised. The narrow divergence (similar to 1 mrad), short pulse duration (similar to 40 ps), high efficiency (similar to 10(-6)) and high brightness (similar to 10(25) photons.s(-1).mm(-2).mrad(-2) of these Ni-like x-ray lasers make them ideal candidates for x-ray laser applications.